Pemanfaatan Lingkungan Lokal dalam Kegiatan Laboratorium Berbasis Inkuiri terhadap Kinerja Mahasiswa Calon Guru Biologi - Marlina, Reni (Jurnal Pendidikan Matematika dan IPA, 2011)
The aim of this research is to compare the inquiry-based laboratory activities by utilizing the local environment with traditional laboratory activities on Environmental Pollution and Biological Diversity to develop a scientific performance pre-service biology teacher. The method of this research was used quasi-experiment research with groups design alternative treatment only post-test nonequivalent. The sample were 2nd semester pre-service biology teacher at biology education department that following the Environmental Science Course at FKIP Tanjungpura University, consist of 40 students. The instrument was used performance assessment. The results show the scientific performance of pre-service biology teacher who use inquiry-based laboratory activities by utilizing local environment was differ significantly with the use of traditional laboratory activities. Keywords: inquiry-based laboratory, traditional laboratory, scientific performance, local environment